Fiscal stimulus in a model with endogenous firm entry - Alexander Totzek; Roland C. Winkler (Kiel University, Department of Economics, 2010)
This paper explores different fiscal stimuli within a business cycle model with an endogenous number of firms. We demonstrate that a changing number of firms is a crucial dimension for evaluating fiscal policy since it accelerates the impacts of fiscal policy. In the presence of demand stimuli fiscal multipliers are small and the number of firms may decline, in particular under distortionary tax financing. Policies that disburden private agents from income taxes, on the other hand, are effective in boosting economic activity and new firm creation.
Keywords: E62; E32; E22; 330; Fiscal Multipliers; Firm Entry; Product Variety; Finanzpolitik; Multiplikator; Konjunkturtheorie; Markteintritt; Dynamisches Gleichgewicht; Theorie